Reversible cerebral vasoconstriction with thunderclap headache: A case report - Ji, Jae Young (Medicine (Baltimore), 2019)
RATIONALE: Reversible cerebral vasoconstriction syndrome (RCVS) is often accompanied by thunderclap headaches. Although symptoms usually resolve spontaneously within 2 months, it can cause fatal complications, such as cerebral hemorrhage, and is difficult to differentiate from a migraine and other headaches on the basis of symptoms and Imaging study. In this case report, we explore clinical findings and appropriate treatment methods for RCVS through the case study of a female patient who experienced severe headache upon defecation PATIENT CONCERNS: A 42-year-old female patient complained of a severe throbbing headache with a Numeric Rating Scale (NRS) score of 10 after defecation. The pain subsided temporarily after treatment with diclofenac 75 mg and Tridol 50 mg propacetamol 1 g, but the headache returned upon defecation; soon after, the patient complained again of regular headaches at 4 to 6-hour intervals irrespective of defecation. DIAGNOSIS: Brain computed tomography (CT) and head and neck magnetic resonance angiography, performed during a headache episode, revealed no specific neurological findings. Blood analysis was also normal. Head and neck CT angiography, performed one month after the start of the headaches, revealed RCVS. INTERVENTIONS: Treatment commenced with pregabalin (150 mg), oxycodone HCl/naloxone (10/5 mg), Alpram (0.5 mg), milnacipran (25 mg), and frovatriptan 25 mg, but there was no improvement in the headaches. The patient received bilateral trigger point injections (TPI) in the temporal muscles on four occasions at the pain clinic. OUTCOMES: Medication showed no effect, but after the patient received four sessions of bilateral TPI in the temporal muscles her NRS score eventually decreased from 10 to 2. The patient is currently continuing medication while still experiencing headaches at reduced intensities. LESSONS: RCVS is difficult to diagnose; moreover, it is difficult differentiate RCVS from other headaches. However, as it can cause fatal complications, it should not be overlooked. It is essential to consider diagnostic treatment for all types of headaches because RCVS can be accompanied by headaches originating from other causes.